The Decision Support System for Selecting the Best Teacher for Birull Walidaini Using the SAW Method - Muqorobin Muqorobin (Institut Teknologi Bisnis AAS Indonesia, 2023)
Birull Walidaini Kindergarten is a learning place for children aged 4 years. In selecting the best teacher at the Birull Walidaini Kindergarten, Sragen there are still several obstacles such as the assessment of each teacher is still done manually, namely the principal must fill out the assessment instrument form for each teacher that has been provided, which causes the assessment process to be inaccurate and inefficient. In addition, to obtain or find out information on the results of selecting the best teacher, it takes quite a long time, because the administration section has to re-enter each teacher's grades into Microsoft Excel and make pranks on teacher grades manually. Data collection methods used are interviews, observation and literature study. The decision-making method used by the author is SAW, while the system development method used is the SDLC method with design tools UML. Implementation of the program using the PHP programming language with MySQL database. Decision support systems can be used to make it easier for schools to manage data, present information, generate reports and reduce errors in calculating grades and get accurate teacher ranking results and the application of the SAW method can improve the quality of decision making in selecting the best teachers. Based on the results of research conducted at the Birull Walidaini Kindergarten, Sragen, the best teacher score was according to the ranking, namely teacher Theresia Luan with a score of 1.00.